2017
DOI: 10.18632/oncotarget.23652
|View full text |Cite
|
Sign up to set email alerts
|

MMP2-A2M interaction increases ECM accumulation in aged rat kidney and its modulation by calorie restriction

Abstract: Age-associated renal fibrosis is related with renal function decline during aging. Imbalance between accumulation and degradation of extracellular matrix is key feature of fibrosis. In this study, RNA-sequencing (RNA-Seq) results based on next-generation sequencing (NGS) data were analyzed to identify key proteins that change during aging and calorie restriction (CR). Among the changed genes, A2M and MMP2, which are known to interact, exhibited the highest between centrality (BC) and degree values when analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…5 I ). In addition, in both of the GFAP‐α‐KO clonal lines, expression of α‐2‐macroglobulin ( A2M ) that binds and inhibits the active form of MMP2 (63) was strongly decreased, and expression was even mostly below detection (Fig. 5 J ).…”
Section: Resultsmentioning
confidence: 99%
“…5 I ). In addition, in both of the GFAP‐α‐KO clonal lines, expression of α‐2‐macroglobulin ( A2M ) that binds and inhibits the active form of MMP2 (63) was strongly decreased, and expression was even mostly below detection (Fig. 5 J ).…”
Section: Resultsmentioning
confidence: 99%
“…MMP knockout mice models have shown increased fibrosis and accelerated kidney disease progression [25]. In contrast, several reports have shown that upregulation of MMPs promote fibrosis [5,[26][27][28] maybe due to interaction with overexpressed TIMPs [27,29] or due to the capacity of MMP degradation products to induce EMT [5,30]. In a study performed by Tan et al, they exposed murine tubular epithelial cells to an activated macrophage conditioned medium.…”
Section: Matrix Metalloproteinases Pathways In the Kidneymentioning
confidence: 99%
“…25 27 Age-related dysregulation of renal extracellular matrix (ECM) in rats has been shown to be associated with the loss of epigenetic gene silencing as well as with decreased matrix metallopeptidase 2 activity. 28 30 However, it is difficult to determine whether alterations to the membrane are actually causal or simply an effect of early damage at the tubulointerstitial interface. Immunochemical investigations have revealed neither immune complexes nor serum antibody are responsible for basement membrane thickening, and serum from rats with advanced CPN are negative for immunoglobulin G (IgG) or IgM antibodies to kidney antigens.…”
Section: Chronic Progressive Nephropathy Pathogenesis From a Historicmentioning
confidence: 99%